On-demand integrated nano-engager converting cold tumors to hot via increased DNA damage and dual immune checkpoint inhibition - Xiaoqing Liu; Shuang Liang; Xiao Sang; Lili Chang; Shunli Fu; Han Yang; Huizhen Yang; Yongjun Liu; Na Zhang (Elsevier, 2023)
Cancer immunotherapy has become a promising strategy. However, the effectiveness of immunotherapy is restricted in "cold tumors" characterized with insufficient T cells intratumoral infiltration and failed T cells priming. Herein, an on-demand integrated nano-engager (JOT-Lip) was developed to convert cold tumors to hot via "increased DNA damage and dual immune checkpoint inhibition" strategy. JOT-Lip was engineered by co-loading oxaliplatin (Oxa) and JQ1 into liposomes with T-cell immunoglobulin mucin-3 antibodies (Tim-3 mAb) coupled on the liposomal surface by metalloproteinase-2 (MMP-2)-sensitive linker. JQ1 inhibited DNA repair to increase DNA damage and immunogenic cell death (ICD) of Oxa, thus promoting T cells intratumoral infiltration. In addition, JQ1 inhibited PD-1/PD-L1 pathway, achieving dual immune checkpoint inhibition combining with Tim-3 mAb, thus effectively promoting T cells priming. It is demonstrated that JOT-Lip not only increased DNA damage and promoted the release of damage-associated molecular patterns (DAMPs), but also enhanced T cells intratumoral infiltration and promoted T cell priming, which successfully converted cold tumors to hot and showed significant anti-tumor and anti-metastasis effects. Collectively, our study provides a rational design of an effective combination regimen and an ideal co-delivery system to convert cold tumors to hot, which holds great potential in clinical cancer chemoimmunotherapy.